Answer:
e^ (5 ln (x + 1)) = (x + 1)^5
Step-by-step explanation:
e5 In (x + 1) or did you mean e^ (5 ln (x + 1))
because then this would simplify a lot
e^ (5 ln (x + 1)) = e ^ (ln (x + 1)^5)
e^ (5 ln (x + 1)) = e ^ (ln (x + 1)^5) = (x + 1)^5
or did you mean (e^5) ( ln (x + 1)) = ln [(x+1)^(e^5)]
But I think you meant:
e^ (5 ln (x + 1)) = e ^ (ln (x + 1)^5) = (x + 1)^5
Answer:
Step-by-step explanation:
6-3x=12-6x
Only one solution of x=2
Answer:
D? maybe, I'm not sure. it jsut makes the most sense.
Nothing else is given, so for the two triangles to be congruent, the only possible proof is the ASA theorem.
first pairs of angles: 2x+7=x+21 => x=14
second pairs of angles: 8y-4=4y+28 =>y=8
The two triangles share the same side PR
Based on the Angle-Side-Angle Triangle Congruence theorem, these two triangles are congruent with x=14, y=8
(2x+7) +(8y-4) +Q=180 =>85
9514 1404 393
Answer:
2 1/12 days
Step-by-step explanation:
Time is the ratio of distance to speed.
(1200 mi)/(24 mi/h) × (1 day)/(24 h) = 25/12 day = 2 1/12 days